Hirshfeld surface and theoretical studies of 2,2,2-trichloro-N,N-bis(2-(2,2,2-trichloroacetamido)phenyl)acetamide compound - Aydogdu, Immihan Sezen; Gumus, Ilkay; Arslan, Hakan (European Journal of Chemistry, 2019)
The vibrational frequencies, atomic charges and the related properties of the 2,2,2-trichloro-N,N-bis(2-(2,2,2-trichloroacetamido)phenyl)acetamide (H2LNNN) were investi-gated by Ab-initio Hartree-Fock (HF) and Density Functional Theory (DFT) methods such as BLYP, B3LYP, B3PW91 and mPW1PW91 functionals with 6-31G(d,p) and 6-311G(d,p) basis sets. The experimentally determined parameters were compared with those calculated theoretically and they were found to complement each other with a very good correlation. The theoretical vibrational spectrum of H2LNNN molecule was interpreted by means of potential energy distributions using the SQM 2.0 program. The Hirshfeld surface analysis was carried out to discuss the role of the hydrogen bonds and other intermolecular contacts in crystal lattice. Hirshfeld surface analysis revealed the occurrence of Cl⋯H, Cl⋯Cl, Cl⋯C, H···H, O⋯H, C···H and Cl···π interactions that display an important role on the crystal packing stabilization of the compound.